Comparison of direct-plating and enrichment methods for isolation of Vibrio cholerae from diarrhea patients. - Lesmana, M (1997)
A direct-plating method on thiosulfate citrate bile salts sucrose agar (DIR-TCBS) in conjunction with enrichment in alkaline peptone water (APW) incubated for both 6 h and 24 h followed by subculture onto TCBS (APW6h-TCBS and APW24h-TCBS, respectively) was performed on 16,034 rectal swab samples for isolating Vibrio cholerae. A total of 2,932 (18.3%) rectal swab samples were positive for V. cholerae O1 biotype El Tor, with the Ogawa serotype constituting 99.2% of the isolates. There were no significant differences in V. cholerae O1 isolation rates between the three culture systems nor between the combinations of any two systems. However, direct plating plus enrichment demonstrated a significantly higher V. cholerae O1 isolation rate than DIR-TCBS alone (P < 0.02). Conversely, enrichment procedure, alone or in combination with DIR-TCBS, yielded significantly more (P < 0.0001) V. cholerae non-O1 isolates than DIR-TCBS alone. The length of incubation time of the enrichment broth, 6 h, offers no significant advantages over 24 h for the isolation of V. cholerae O1 and non-O1. A 24-h enrichment broth incubation period has the practical advantage of being easy to integrate into a normal laboratory workday, whereas 6-h broth enrichment, although more commonly recommended, requires that arrangements be made for after-hours subculture.